CULTIVO DE MELANCIA EM SISTEMA DE SEMEADURA DIRETA NA COVA COM USO DE POLIMERO RETENTOR DE ÁGUA - Nunes, Igor Barros,; Espindola, Gabriella Almeida dos Santos,; Silva, Pedro Henrique Ortiz3,; VIEIRA, Jéssica Dionizio,; Rego, Norton Hayd, (ANAIS DO ENIC, 2025)
-